2021
DOI: 10.4049/jimmunol.2001318
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomic Profiles in the Intestine of Shrimp Infected by White Spot Syndrome Virus and Antiviral Function of the Metabolite Linoleic Acid in Shrimp

Abstract: White spot syndrome virus (WSSV) is a threatening pathogenic virus in shrimp culture, and at present, no effective strategy can prevent and control the disease. Intestinal flora and its metabolites are important for the resistance of shrimp to lethal pathogenic viruses. However, the changes of metabolites in the shrimp intestines after WSSV infection remain unclear. We established an artificial oral infection method to infect shrimp with WSSV and analyzed the metabolites in intestinal content of shrimp by HPLC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 52 publications
1
16
0
Order By: Relevance
“…In the virological field, the first metabolomics study was reported in 2006, and analyzed over sixty metabolites during human cytomegalovirus infection (Munger et al, 2006). Since then, a variety of viruses have been demonstrated to alter multiple metabolic pathways in cells, like glycolysis and fatty acid synthesis, and have expanded the number of cellular metabolites (Birungi et al, 2010;Ritter et al, 2010;Hollenbaugh et al, 2011;Delgado et al, 2012;Sanchez et al, 2017;Tian et al, 2019;Li et al, 2021;Nunes et al, 2021;Pant et al, 2021;Wang et al, 2021). We have constructed a wild-type SVA (CH-LX-01-2016) using reverse genetics (Liu et al, 2021a), and more recently have revealed a proteomic profile of BSR-T7/5 cells inoculated with this virus at 12 hpi (Liu et al, 2021b).…”
Section: Introductionmentioning
confidence: 99%
“…In the virological field, the first metabolomics study was reported in 2006, and analyzed over sixty metabolites during human cytomegalovirus infection (Munger et al, 2006). Since then, a variety of viruses have been demonstrated to alter multiple metabolic pathways in cells, like glycolysis and fatty acid synthesis, and have expanded the number of cellular metabolites (Birungi et al, 2010;Ritter et al, 2010;Hollenbaugh et al, 2011;Delgado et al, 2012;Sanchez et al, 2017;Tian et al, 2019;Li et al, 2021;Nunes et al, 2021;Pant et al, 2021;Wang et al, 2021). We have constructed a wild-type SVA (CH-LX-01-2016) using reverse genetics (Liu et al, 2021a), and more recently have revealed a proteomic profile of BSR-T7/5 cells inoculated with this virus at 12 hpi (Liu et al, 2021b).…”
Section: Introductionmentioning
confidence: 99%
“…[35][36][37] WSSV infection significantly alters expression of fatty acids, amino acids, energy-related metabolites and the gluconeogenesis pathway, 38 as well as changing glycerophospholipid metabolism and upregulating the biosynthesis of unsaturated fatty acids, including linoleic acid. 39 Interestingly, the upregulated linoleic acid induces the expression of several antimicrobial peptides and immune genes that activate the ERK-NF-κB pathway, suggesting that the altered metabolites not only benefit the viral replication but can also induce an antiviral immune response. 39 Lastly, we note that WSSV infection also upregulates mitochondrial ATPase inhibitor factor 1 (ATPIF1), and that treatment with recombinant ATPIF1 protein induces superoxide production and NF-κB activation, both of which facilitate WSSV replication.…”
Section: Wssv Modulates Host Metabolism For Survival and Replicationmentioning
confidence: 99%
“…Lysosome ( Lyz1 ), another canonical anti-bacterial enzyme, is a well-known macrophage secreting hydrolase(Short, Nickel, Schmitz, & Renkawitz, 1996). Vago5 , an IFN-like anti-viral cytokine, plays its roles during anti-WSSV process(C. Li, Yang, Hong, Zhao, & Wang, 2021)( Figure 1C; figure supplement 2B ). In general, this group of cells were featured with their secretion of anti-bacterial and anti-viral effectors.…”
Section: Resultsmentioning
confidence: 99%